The importance of using movies in teaching and learning the English language in ESL classroom - PhD, docent Rustamova Adash Eshankulovna; Student, Sharifova Diyora Sharofjon qizi (Zien Journals, 2023)
Nowadays, due to the fact that we are living in the era of technology, teachers are required to use interactive and innovative methods in the classroom. Movie or film is one of the crucial part in the teaching process so that it can improve learners English skills. English films can help students to enhance their listening and speaking competences, their creativity and social backgrounds. This article describes the importance of films that are used as a teacher aid in order to teach the English language for ESL learners.
Keywords: technology; films; language instruction; classroom interaction